Localizing pharmaceuticals manufacturing and its impact on drug security in Saudi Arabia - Essam A. Tawfik; Abdulkader F. Tawfik; Areej M. Alajmi; Moutaz Y. Badr; Ahmed Al-jedai; Nada H. Almozain; Haitham A. Bukhary; Abdulrahman A. Halwani; Saeed A. Al Awadh; Aws Alshamsan; Salim Babhair; Abdulaziz M. Almalik (Elsevier, 2022)
Local production of pharmaceuticals plays a vital role in maintaining resilience of national healthcare systems, especially when it comes to facilitating access to needed medicines and decreasing exposure to imports and international supply chains. Pharma is a research-intensive industry and the systemic lack of governance and support to R&D activities in this sector, among other host of related issues such as unsupportive regulatory regimes and human resources capacity limitations, is one of the major impediments to the diversifying of locally produced pharmaceuticals portfolio. In this review, an overview of the current pharmaceutical production system in Saudi Arabia, its major challenges, and proposed remedies to address them will be highlighted.